The Productivity of Low‐Elevation Juniper Forests in Central Asia Increased Under Moderate Warming Scenarios. Issue 4 (21st April 2021) - Chen, Feng; Yu, Shulong; Shang, Huaming; Zhang, Ruibo; Zhang, Tongwen; Zhang, Heli; Chen, Youping; Satylkanov, Rysbek; Ermenbaev, Bakytbek; Kobuliev, Zainalobudin; Ahmadov, Ahsan; Kodirov, Anvar; et al.
Abstract: Clear trends of warming and wetting have occurred in Central Asia during the last 30 years, but how tree growth in low‐elevation mountainous areas has responded to climate warming remains unclear. In this paper, we investigated the relationships between Zeravschan juniper ( Juniperus seravschanica ) growth and climate factors based on 16 tree‐ring chronologies from low‐elevation mountainous areas across Central Asia and then used the resulting model to predict changes in Zeravschan juniper growth during the 21st century. Zeravschan juniper growth in our study region is mainly controlled by precipitation, which is predominantly influenced by tropical sea surface temperatures. The combination of increased precipitation and warm temperatures promoted the growth of Zeravschan juniper during the recent warm period. Our simulations suggest that Zeravschan juniper growth will still increase slightly under the RCP4.5 and RCP8.5 scenarios in the next 30 years, possibly due to increased precipitation caused by climate warming; however, climate warming will initially show negative effects and is expected to have greater effects after the 2050s. Better knowledge regarding regional climate mechanisms and their likely influences on tree growth is useful for improving forest planning and management in Central Asia. Key Points: Warm‐wet conditions have caused an increase in Zeravschan juniper growth since the 1980s Zeravschan juniper growth was controlled by tropical SST‐induced precipitation High greenhouse gas emissions have a negative effect on juniper tree growth in Central Asian low‐elevation areas